ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TEPUNG DENGAN METODE EOQ PADA INDUSTRI KECIL MENENGAH (Studi pada Kue Kacang Tiga Saudara Tanah Datar) - Aziz Fadhel; Marpaung J.M. Rio; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted with the aim of knowing the optimal quantity of flour raw material purchases at Tiga Saudara's company, the frequency of purchasing raw materials, the amount of safety stock, determining the reorder point and the total cost of the flour raw material inventory. using the Economic Order Quantity method. The object of this research is the Tiga Saudara Tanah Datar company. Sources of data obtained by interview observation and documentation. This type of research used by the author is descriptive research using a quantitative approach. The results of the analysis show that if the company applies the Economic Order Quantity method in 2015, 2016, 2017, 2018 and 2019 for the optimal purchase of flour raw materials, the difference in savings in the total cost of raw materials for flour 2015-2019 is IDR 232,521, IDR 228,902. IDR 233,580, IDR 232,531 and IDR 250,419. Based on the results that have been analyzed using the Economic Order Quantity method, the company should use this method in determining optimal raw material purchases so that the Tiga Saudara company can minimize the total inventory costs incurred for the coming period.Keywords: Economic Order Quantity Method, Raw material inventory